Novel combustion synthesis of carbon foam‑aluminum fluoride nanocomposite materials - Kostoglou, Nikolaos; Emre Gunduz, I.; Isik, Tugba; Ortalan, Volkan; Constantinides, Georgios; Kontos, Athanassios G.; Steriotis, Theodore; Ryzhkov, Vladislav; Bousser, Etienne; Matthews, Etienne; Doumanidis, Etienne; Mitterer, Christian; et al. (My University, 2018)
The facile, rapid and bulk production of composite materials consisting of carbon nanostructures doped with metal-based compounds has been a significant challenge for various research areas where such types of materials can be applied, including catalysis, energy storage and water purification. In this work, a carbon foam‑aluminum fluoride composite (C-AlF3) was developed by adopting a combustion synthesis approach, which is an attractive alternative to wet chemical methods usually employed for such purposes. The flame ignition and combustion of a solid-state mixture comprising a fluoropolymer and nano-sized Al powder leads to the formation of a porous carbon foam network doped with dispersed cubic-like AlF3 nanoparticles (100 to 500 nm in size), as observed by high-resolution microscopy methods. Selective area electron diffraction and X-ray diffraction studies revealed a rhombohedral α-AlF3 crystal structure for these embedded particles, while micro-Raman spectroscopy indicated typical carbonaceous features for the foamy matrix. The C-AlF3 composite also showed a combination of micro-, meso- and macro-porous characteristics (i.e. pore sizes in the nanometer scale) based on the analysis of N2 sorption data collected at 77 K. The findings of this study provide useful insights for further research on carbon-based nanocomposite materials prepared via direct combustion synthesis routes.
Keywords: Aluminum fluoride; Carbon foam; Combustion synthesis; Nanocomposite; Porous material